Evaluation of pore-throat structures of carbonate reservoirs based on petrophysical facies division - Hou, Jue; Zhao, Lun; Zhao, Wenqi; Feng, Zhao; Wang, Xueke; Zeng, Xing (Frontiers in Earth Science, 2023)
After complex geological transformation, such as sedimentation, diagenesis and tectonic transformation, carbonate reservoirs have developed multiple reservoir spaces with significant heterogeneity and various pore-throat structures, including pores, vugs and fractures. Due to these characteristics, many problems have been caused during the development of the carbonate reservoirs, such as large differences between the initial production capacities of single wells, and serious water channeling after injection, which has brought many challenges to the efficient development of the carbonate reservoirs. Therefore, based on a reservoir evaluation method of petrophysical facies, this study classified and evaluated the pore-throat structures of Carboniferous carbonate reservoirs in the North Truwa Oilfield of the Pre-Caspian Basin. Based on the data of core, thin section, scanning electron microscope, high-pressure mercury injection, sedimentary facies, diagenetic facies and the development of fractures and karst vugs, six reservoir petrophysical facies in the study area were classified and named, including the facies of favorable deposition-constructive diagenesis-fracture and vug, the facies of favorable deposition-constructive diagenesis-non fracture or vug, the facies of favorable deposition-destructive diagenesis-fracture and vug, the facies of favorable deposition-destructive diagenesis-non fracture or vug, the facies of unfavorable deposition-constructive diagenesis-non fracture or vug, the facies of unfavorable deposition-destructive diagenesis-non fracture or vug. The recognition and division of diagenetic facies were based on the K Nearest Neighbor (KNN). Four quantitative parameters were also selected to characterize the pore-throat structures, including displacement pressure (P_d), mercury removal efficiency (E_m), median throat radius (R_50), and sorting coefficient (C_s). Based on the Principal Component Analysis (PCA), the classification and evaluation standards of pore-throat structures in different petrophysical facies were established. Combined with the flow profile measured by production logging tools, the relationship between different petrophysical facies and productions was also revealed. As a result, this study can provide suggestions for the adjustment strategy of water drive production, which lays an important foundation for the fine development of carbonate reservoirs.